Centrifuge Tests on Vertical Bearing Capacity of Jacket Pile Foundation in Clay Seabed Under Different Grouting Effects - SONG Junlin, LIU Bo, TANG Liheng, LIAO Chencong (Shanghai Jiaotong Daxue xuebao)
Jacket foundations are often used as the main support structure for offshore wind turbines in waters with a depth of 40—60 meters. The jacket foundation is connected to the top of the pile foundation through underwater high-strength grouting to form a top sealing section, which together bears the vertical load. In this paper, centrifugal model tests are conducted for three different grouting effects: normal grouting at the top of a pile foundation, insufficient grouting, and poor grouting with through-holes. The vertical bearing capacity of the foundation and the bearing capacity sharing ratio between the grouting section and the pile body section under the limit state are analyzed, and compared with existing theoretical calculation methods. The results show that the bearing capacity of the grouting sealing cap depends on the sealing effect. For foundations with normal grouting and insufficient grouting of grouting sealing caps, the bearing capacity of grouting sealing caps accounts for approximately 25%—30% of the total bearing capacity of the foundation. When there are through-holes in poor grouting, the bearing capacity of the foundation grouting section develops early and quickly reaches its limit, whose sharing ratio is far lower than the other two bearing capacities. The test results in this paper can provide a reference for the calculation of bearing capacity in foundation design.